Do firms manage their CSR reputation? Evidence from Twitter - CROWLEY, Richard M. (Institutional Knowledge at Singapore Management University, 2019)
Using a machine learning approach to process 11 million tweets posted by S&P 1500 firms from 2011 through 2016, we find that poor CSR performance firms tweet more about CSR activities and use tweets that are shorter, and with more passive voice and extreme tone. Good CSR performance firms tweet less about CSR, yet gain twice more followers per CSR tweet than poor CSR performance firms. Good CSR performance firms also experience a greater decrease in institutional ownership along with higher increases in bid-ask spread and stock return volatility after joining Twitter than do poor CSR performance firms. Our findings suggest that poor CSR performance firms play a greenwashing strategy, but this strategy is not effective in leading to capital market consequences.